Types of Feminism in Poem “Menghapus Katanya” by Maudy Ayunda - Paramita Dharmayanti, Putu Ayu; Ari Wiryadi Joni, Dewa Ayu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
This research is qualitative research focusing on finding out the types of feminism in poem “Menghapus Katanya” by Maudy Ayunda. It reveals that this poem talks about feminism based on four types of feminism. Based on Liberal Feminism, this poem points out that man and woman have same right especially in education. Related to Marxist Feminism, this poem emphasizes that woman has right in economic in term of working to earn money. From Socialist Feminism view, this poem stresses out that man and woman have equal status. The last, based on Radical Feminism, this poem argues that woman has to be braver and stronger. This poem is really inspired women to speak and act toward feminism and have motivation to be a better version of woman.